Manajemen Kurikulum Ismuba Berbasis Boarding School di SMA Muhammadiyah Wonosobo - Addinia Rizki Sabili; Hendro Widodo (Ta'allum: Jurnal Pendidikan Islam, 2019)
The existence of formal schools under the auspices of bording school foundation has its own uniqueness compared to other schools in general. One of the models is Boarding School of Muhammadiyah Wonosobo High School. This article aims to describe in depth the Ismuba curriculum management based on Boarding School. This research type is field research naturally. This qualitative research departs from certain cases and conditions so isn’t use term population. Qualitative research uses the term social situation which consists of places, actors, activities that are integrated with each other. Data is collected by interviewing, documenting, and observing. The results of this research can be summarized as follows: (1) The management of "boarding school" Islamic education in Wonosobo Muhammadiyah High School appears in the management process starting from planning, organizing, acting, and controlling (POAC) (2) Management of Islamic boarding school education on weekly or monthly target. (3) A supporting factor in  implementation of "boarding school" education management is the integration of general education and Islamic education.